2005
DOI: 10.1186/1743-422x-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional VOPBA reveals laminin receptor (LAMR1) interaction with dengue virus serotypes 1, 2 and 3

Abstract: Background: The search for the dengue virus receptor has generated many candidates often identified only by molecular mass. The wide host range of the viruses in vitro combined with multiple approaches to identifying the receptor(s) has led to the notion that many receptors or attachment proteins may be involved and that the different dengue virus serotypes may utilize different receptors on the same cells as well as on different cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Sindbis virus uses LamR as a functional receptor to enter BHK-21 cells (39). Mosquito LamR was found to be a putative receptor for Venezuelan equine encephalitis virus (40) and dengue virus (41)(42)(43)(44). In mammalian cells, LamR acts as a cellular receptor for the cellular prion protein (PrP) (45,46), and it mediates the infection of adeno-associated virus serotypes 8, 2, 3, and 9 (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sindbis virus uses LamR as a functional receptor to enter BHK-21 cells (39). Mosquito LamR was found to be a putative receptor for Venezuelan equine encephalitis virus (40) and dengue virus (41)(42)(43)(44). In mammalian cells, LamR acts as a cellular receptor for the cellular prion protein (PrP) (45,46), and it mediates the infection of adeno-associated virus serotypes 8, 2, 3, and 9 (47).…”
Section: Discussionmentioning
confidence: 99%
“…These membrane proteins were low-density lipoprotein receptor (LDLr), LamR, and vinculin. Among these, LamR has been identified to be a cellular receptor for different pathogens (38)(39)(40)(41)(42)(43)(44)(45)(46)(47). As shown in Fig.…”
Section: Membrane Proteins Required For Csfv Infection Were Screened mentioning
confidence: 99%
“…This may suggest that dengue virus serotype 2 is capable of only binding to a denatured form of the laminin-binding protein. One other group has recently identifi ed the 37/67-kDa high-affi nity laminin receptor protein as a dengue virus-binding protein [31] . This group also showed that binding to the 37/67-kDa high-affi nity laminin receptor was serotype specifi c, and noted that dengue serotypes 1, 2 and 3, but not serotype 4, bound to the 37/ 67-kDa high-affi nity laminin receptor expressed by PS Clone D cells, raising the possibility that the binding between the dengue viruses and the 37/67-kDa high-affi nity laminin receptor may not only depend upon viral factors, but may also be infl uenced by specifi c posttranslational modifi cations of the 37/67-kDa high-affi nity laminin receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out to identify molecules involved in dengue virus–host interactions. Independent studies have shown that different proteins, including high-affinity laminin receptor [10,11], CD14-associated protein [12], and other, uncharacterized, proteins [13] might be involved in dengue virus–host cell interactions. However, it has been reported that most of these molecules are not involved in dengue virus high-affinity interaction or internalization [14].…”
Section: Introductionmentioning
confidence: 99%